Complex quaternary hydrides Mg2(Fe,Co)Hy for hydrogen storage - Meyer, Marcos (2011)
Complex ternary hydrides based in Mg and transition metals are very attractive materials for hydrogen and energy storage due to their large volumetric capacity, up to 150 kgH2/m3 in Mg2FeH6 and their high dissociation enthalpies. These compounds may be produced at room temperature by mechanical milling of the constituents in H2 atmosphere. This technique has also served to explore the synthesis of quaternary hydrides Mg2T1-zT’zHy, combining two transition metals to optimize the properties of the resulting hydride. In the present work we analyze the mechanical synthesis of the compounds Mg2Fe1-zCozHy (z = 0, ¼, ½, 3/4, 1) by mechanical alloying at room temperature Mg-Fe-Co powder mixtures in adequate proportion, at 0.3 MPa H2. We follow the mechanosynthesis process trough the analysis of the hydrogen absorption kinetic curves. Samples obtained after a steady state was reached were characterized by X ray diffraction and Mossbauer spectroscopy. The different stages in the mechanosynthesis of these complex hydrides are discussed in terms of the composition and initial state of the powder mixture.